The effect of a training program using the hypoxic mask on some aerobic and anaerobic abilities For under-19 footballers - bentoumia, Radhouane; bengoua , ali (sports creativity, 2025)
The study aimed to identify the effect of a training program using a hypoxic training mask on some basic capabilities (VMA / VO2max, RSA and muscle strength) for soccer players, and to achieve the goals of this research and to answer its questions and achieve its hypotheses, the researchers used the experimental method to study the effect of the mask on the capabilities of players Physical, as the sample was chosen intentionally, which included 20 footballers ranked under 19 years for the Jebel Tiaret team, the players were selected 10 players, a control sample and 10 players, a pilot sample with the exception of a goalkeeper position for its specificity, and the study tools included the use of modern sources and references, Yoyo tests VMA, RSA speed efficiency test, and myotest test to measure the muscular strength of the two men, and the same training program was applied to the experimental and control samples with the use of the mask for the experimental sample during eight weeks, and after collecting the results we analyzed and discussed and concluded that there were statistically significant differences in the tribal measurement and Dimension of the experimental and control groups in measuring the aerobic and anaerobic capacity for the benefit of the experimental sample for football players under 19 Year